Growth of Assam Gramin Vikash Bank in Credit Deployment: An Analysis - Kashyap, Pinkumoni; Adhikari , Kingshuk; Dey, Nikhil Bhusan (Gyan Management Journal, 2015)
This paper seeks to examine the growth of outstanding advances of Assam Gramin Vikash Bank for a period of nine years from 2006 to 2014. In order to analyze growth, total advances, advances to priority sector, non priority sector, Agriculture & Allied, SSI/MSME, Service & Other and Housing have been considered. The results have been derived from the use of statistical tools like Yo Y Growth Rate, Compound Annual Growth Rate (CAGR), t-test, Kolmogorov-Smirnov Test & Shapiro-Wilk Test and ANOVA. The study reveals that Assam Gram in Vikash Bank has made considerable growth in terms of credit deployment.